2019
DOI: 10.1371/journal.pone.0221466
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability of quantitative measurements of retinal layers with SD-OCT and agreement between vertical and horizontal scan protocols in healthy eyes

Abstract: Purpose To evaluate the repeatability of the new spectral domain optical coherence tomography (HOCT-1F), and also to evaluate the agreement between vertical and horizontal scan protocols. In addition, we also evaluated the relation between the repeatability and age. Methods Three consecutive measurements of the inner limiting membrane–retinal pigment epithelium (ILM-RPE), inner limiting membrane–inner plexiform layer (ILM-IPL) from macular horizontal and vertical scans,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 30 publications
3
18
0
Order By: Relevance
“…18 For the HOCT-1F, the intra device repeatability of the macular thickness measurement has been shown to be good, although dependent of the direction of the scan (ie, horizontal vs vertical scan). 21 Macular thickness findings reported in other studies are similar to our data (Table 5), we also found that men have a greater macular thickness than women and the temporal macular area has thinner values. A limitation of this study was that the majority (68.7%) of the individuals were • Men had greater retinal thickness in all inner areas (P<0.001)…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…18 For the HOCT-1F, the intra device repeatability of the macular thickness measurement has been shown to be good, although dependent of the direction of the scan (ie, horizontal vs vertical scan). 21 Macular thickness findings reported in other studies are similar to our data (Table 5), we also found that men have a greater macular thickness than women and the temporal macular area has thinner values. A limitation of this study was that the majority (68.7%) of the individuals were • Men had greater retinal thickness in all inner areas (P<0.001)…”
Section: Discussionsupporting
confidence: 92%
“…The current study obtained CST values from a healthy Mexican population using the HOCT-1F unit, which was recently launched on the market and has undergone limited evaluations. 21 Table 5 summarizes macular thickness data obtained from a sample of 12 studies (including this study) evaluating several populations in 11 different countries with different OCT units. Seven of these studies had a population that was older than 40 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, there are several OCT instruments available for clinical use, each includes its own segmentation algorithm software to delineate the retinal layers. Precision studies are needed to know how consistent the measurements of the retinal layers are, since the precision depends on the segmentation algorithm, scan resolution, scan direction, and acquisition time [ 16 19 ]. Modern OCT devices allow the clinician to customize the scan settings, such as the number of A- and B-scans, scan length, or scan direction.…”
Section: Introductionmentioning
confidence: 99%
“…These parameters are helpful to monitor disease progression because repeated measurements are performed over time at the same anatomical region of an individual patient. Both SD-OCT and SS-OCT have demonstrated repeatability and reproducibility for clinical use 4 7 , which is an important reason for the widespread use of OCT in the diagnosis and management of various ocular conditions, including glaucoma.…”
Section: Introductionmentioning
confidence: 99%